Multicenter Patch Testing With Methylchloroisothizoline/Methylisothiazolinone in 100 and 200 ppm Within the International Contact Dermatitis Research Group. Issue 3 (May 2017) - Engfeldt, Malin; Ale, Iris; Andersen, Klaus E.; Elsner, Peter; Goh, Chee-Leok; Goossens, An; Jerajani, Hemangi; Matsunaga, Kayoko; Bruze, Magnus
Abstract : Background: The preservative methylchloroisothiazolinone/methylisothiazolinone (MCI/MI) is a well-known contact sensitizer. Historically, there have been different opinions on the optimal patch test concentration of MCI/MI, and both 0.01% and 0.02% aqueous (aq.) have been proposed. In 2011, based on literature reviews, it was recommended that the concentration of 0.02% aq. should be used in the international baseline series. Objectives: The aim of this study was to verify the recommendation from 2011 by comparing the patch test results from consecutive patch testing with MCI/MI 0.01% and 0.02% in clinics representing countries around the world. Patients and Methods: Two thousand seven hundred three consecutive patients with dermatitis in 8 dermatology clinics representing 8 countries were patch tested with MCI/MI 0.01% aq. and, in parallel with MCI/MI 0.02% aq., provisionally included in the baseline series. Results: Contact allergy to MCI/MI at 0.01% and 0.02% was found in 3.7% and 5.6% of the patients, respectively ( P < 0.001). Conclusions: Methylchloroisothiazolinone/MI 0.02% aq. (dose, 6 μg/cm 2 ) diagnoses significantly more contact allergy than 0.01% (dose, 3 μg/cm 2 ), without resulting in more adverse reactions. Methylchloroisothiazolinone/MI at 0.02% aq. should therefore be continuously used in the international baseline series.